THE IMPLEMENTATION OF MERDEKA CURRICULUM ON IMPROVING THE QUALITY OF LEARNING THROUGH THE UTILIZATION OF TECHNOLOGY MEDIA AT MA MANBAUL ULUM - Noviatus Sa’diyah (STAI Ma'had Aly Al-Hikam Malang, 2025)
Merdeka Curriculum was introduced as an alternative strategy to create a more independent learning process. This study aims to analyze the implementation of Merdeka Curriculum in improving the quality of learning. This research uses a qualitative approach, with data obtained in the form of spoken words from various sources, such as school principal, curriculum deputy head, teachers, and students. The methods used in this study include the observation, involvement, and speaking methods. The researcher directly listens to the interactions between students and teachers during the teaching and learning process, as well as conducts interviews with the school principal, curriculum deputy head, teachers, and students, supplemented with recording and note-taking techniques. The collected data was transcribed into written form. Next, the researcher performs data reduction by selecting information relevant to the research objectives. After that, the data was classified based on its type and verified through consultations with the school principal, curriculum deputy head, teachers, and language experts. The verified data was then coded in a table format to facilitate further analysis. Finally, the researcher interprets the data obtained and draws conclusions. The results of the study show that the implementation of Merdeka Curriculum at MA MU has successfully utilized technology media, such as educational videos, Google Classroom, and educational games. Some key findings from this study include: first, the media used in learning include educational videos, Google Classroom, and educational games. Second, the teaching and learning process becomes more flexible, both in terms of time allocation and learning materials. Third, technology media such as Google Classroom was used to manage learning efficiently, educational videos enrich the learning experience, and educational games make learning more interactive and enjoyable. Fourth, the use of technology makes it easier to understand learning materials and helps students better comprehend the concepts being taught. Additionally, technology also increases student engagement during the teaching and learning process. Therefore, the results of this study show that the utilization of technology media plays a crucial role in supporting the implementation of Merdeka Curriculum at MA MU, with a positive impact on the quality of learning and student involvement.